2018
DOI: 10.1002/adma.201705544
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Conductivity of Polymers and Their Nanocomposites

Abstract: Polymers are usually considered as thermal insulators, and their applications are limited by their low thermal conductivity. However, recent studies have shown that certain polymers have surprisingly high thermal conductivity, some of which are comparable to that in poor metals or even silicon. Here, the experimental achievements and theoretical progress of thermal transport in polymers and their nanocomposites are outlined. The open questions and challenges of existing theories are discussed. Special attentio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
334
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 542 publications
(336 citation statements)
references
References 146 publications
(289 reference statements)
2
334
0
Order By: Relevance
“…The filler, as an additive to increase the thermal conductivity, is also crucial in controlling thermal conductivity of composite. Most of the researches on low filler content composites are focused on the percolation network of filler, in which the fillers within matrix are connected and creates pathway for phonon or electron to easily transfer the heat 217,223 . When the percolation network exists within the matrix, the thermal conductivity is exponentially increased, which usually occurs around 10-20 wt% of conductive filler 223 .…”
Section: Thermal and Electrical Conductivitymentioning
confidence: 99%
“…The filler, as an additive to increase the thermal conductivity, is also crucial in controlling thermal conductivity of composite. Most of the researches on low filler content composites are focused on the percolation network of filler, in which the fillers within matrix are connected and creates pathway for phonon or electron to easily transfer the heat 217,223 . When the percolation network exists within the matrix, the thermal conductivity is exponentially increased, which usually occurs around 10-20 wt% of conductive filler 223 .…”
Section: Thermal and Electrical Conductivitymentioning
confidence: 99%
“…However, thermal conductivity of most polymers is very low, which might lead to serious problems for device applications such as heat dissipation failure, especially for the organic electronic devices. Previous studies have shown that the low thermal conductivity in polymers mainly comes from the amorphous structures and weak interchain interactions . Therefore, in order to tailor the heat conduction in conductive polymers, it is of great importance to understand the thermal transport mechanisms in conductive polymers.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the low thermal conductivity in polymers mainly comes from the amorphous structures and weak interchain interactions. [21][22][23] Therefore, in order to tailor the heat conduction in conductive polymers, it is of great importance to understand the thermal transport mechanisms in conductive polymers.…”
mentioning
confidence: 99%
“…In order to maintain performance and reliability of electronic devices, it is of great importance for the heat generated by billions of tiny transistors during operation to be efficiently dissipated as soon as possible. Consequently, manufacturing electronic packaging or supporting materials with high thermal conductivities to cool down electronic devices is an essential prerequisite …”
Section: Introductionmentioning
confidence: 99%